2013
DOI: 10.21608/jappmu.2013.71335
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Live Yeast Feed Additives on Productive Performance of Growing Rahmany Lambs.

Abstract: This study was carried out to evaluate the effects of adding two levels of Rumi live yeast (RLY), which is a commercial probiotic containing yeast on productive performance of Rahmany lambs. Twenty-one Rahmany lambs after weaning at three months of age with an average live body weight of 19.33±0.2 Kg were assigned to three groups according to live body weight (7 lambs each). They were randomly assigned to the three experimental diets. The control group was fed 35% corn silage and 65% concentrate feed mixture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
3
0
0
Order By: Relevance
“…The improvement of economical efficiency values being 100, 131, 127 and 133% for T 1 , T 2 , T 3 and T 4 , respectively. Results obtained by this study are in agreement with those obtained by Kholif et al (2009) who worked with dairy cows and using thiamin supplement, El-Shanti et al (2012) who used lambs with thiamin supplement, Mehrez et al (2013) who tested live yeast supplement (good source of Vit. B complex) on grown lambs performance and lastly Mostafa et al (2015) who worked with Friesian calves with different levels of either niacin or thiamin supplements.…”
Section: Blood Parameterssupporting
confidence: 92%
“…The improvement of economical efficiency values being 100, 131, 127 and 133% for T 1 , T 2 , T 3 and T 4 , respectively. Results obtained by this study are in agreement with those obtained by Kholif et al (2009) who worked with dairy cows and using thiamin supplement, El-Shanti et al (2012) who used lambs with thiamin supplement, Mehrez et al (2013) who tested live yeast supplement (good source of Vit. B complex) on grown lambs performance and lastly Mostafa et al (2015) who worked with Friesian calves with different levels of either niacin or thiamin supplements.…”
Section: Blood Parameterssupporting
confidence: 92%
“…The DCP% was significantly (P<0.05) enhanced by the addition of Rumi yeast culture. These results are in agreement with the those obtained by Komonna (2007) and Helal and Abdel-Rahman (2010) and Mehrez et al (2013) who reported that the values of TDN and DCP% were significantly (P<0.05) improved when supplementing diets with yeast culture and commercial probiotic.…”
Section: Effect Of C:r Ratio and Ry Supplementation (Rys) On Nutrientsupporting
confidence: 93%
“…The results in Table (3) showed that the digestibility coefficients of OM, CP, CF, EE and NFE were significantly higher (P<0.05) with RY supplemented (RYS) diet than unsupplemented one (USRY). The obtained results match with those of Paryad and Rashidi (2009), Mousa et al (2012) and Mehrez et al (2013) who found that lambs fed diets supplemented with RLY had higher nutrients digestibility than unsupplemented ones .…”
Section: Effect Of C:r Ratio and Ry Supplementation (Rys) On Nutrientsupporting
confidence: 90%